Simulation: Best Practices in Nursing Education - Moran, Vicki (Springer International Publishing, 2018)
This book focuses on evidence-based standards for simulation in nursing education. The foundational principle of simulation excellence and its relevance to nursing is defined and infuses throughout the book. It also discusses necessary components for quality simulation from development to implementation. These areas include (but are not limited to): theoretical background, accreditation and approval standards, the simulation environment, developing and implementing simulations, and debriefing. These subject areas are approached following a thorough review of the literature and current practices identified from the International Nursing Association for Clinical Simulation and Learning (INACSL), Society for Simulation in Healthcare (SSH), National League for Nursing (NLN) and State Boards of Nursing. This quick reference title will become the best practice standards for simulation excellence in nursing education. .